Hygienic Status in Domestic Fish Trade of Mumbai, India with Special Reference to Salmonella Contamination - Sahu, Bmndaban; Singh, S.D.; Behera, B.K.; Gopal, R.N (Fishery Technology, 2025)
An attempt has been made to study the prevailing hygienic status in domestic fish trade with special emphasis on pathogenic Salmonella contamination. In this study samples of fish, prawn and fish handling environments obtained from retail fish markets, fish landing centres and processing plants of Mumbai, India were analysed for total bacterial load and also for incidence of salmonella. The Total Plate Count (TPC) of different samples varied between 3.28 log cfu/g and 7.04 log cfu/ g. The TPC level in fish and prawn samples from fish landing centres and fish markets were always on higher side and varied between 5.87 and 7.04 log cfu/g. More than 18 % of the samples from the fish markets were contaminated with Salmonella, while none of the fish or shrimp samples from landing centres or the processing plants was found to be contaminated. A total of 26 Salmonella strains, belonging to 11 serovars, were isolated, of which as high as 9 serovars were isolated from different samples of fish markets. Most of the serovars isolated in this study were pathogenic in nature and reported to be responsible for food-borne gastroenteritis in human. Polymerase Chain Reaction (PCR) analysis to test the pathogenicity of the isolated strains confirmed their invasive nature. Looking at the extent of Salmonella contamination with variety of serovars and probable contamination with other pathogens in the samples of fish markets, the domestic retail outlets, a great deal of care is suggested while preparation of such contaminated fish.